A Novel Projection Technique with Detail Capture and Shape Correction for Smoke Simulation. (6th May 2013) - Wu, Xiaoyue; Yang, Xubo; Yang, Yang
Abstract: Smoke simulation on a large grid is quite time consuming and most of the computation time is spent on the projection step. We present a novel projection method which produces quite similar visual results as those produced with the traditional projection method, but uses much less computation time. Our method includes two steps: detail‐capture and shape‐correction. The first step preserves most of the smoke details using an efficient DST (Discrete Sine Transformation) Poisson Solver with auxiliary boundary sweeping. The second step maintains the overall flow shape by solving a correcting Poisson equation on a coarse grid. Our algorithm is very fast and quite easy to implement. Experiments show that our projection is approximately 10–30 times faster than the traditional projection with PCG(Preconditioned Conjugate Gradient), while convincingly preserving both the flow details and the overall shape of the smoke.